Outcomes of Worsened Left Ventricular Ejection Fraction After Transcatheter Aortic Valve Replacement - Hu Z; Wang C; Luo S; Yang B; Zheng S; Hu X; Sun Y; Chen J; Fu M; Fan R; Luo J; Li J (International Journal of General Medicine)
Ziyang Hu,1,* Changjin Wang,2,* Songyuan Luo,2,* Bangyuan Yang,2 Shengneng Zheng,3 Xiaolu Hu,2,4 Yinghao Sun,2 Jiaohua Chen,2 Ming Fu,2 Ruixin Fan,5 Jianfang Luo,2,4 Jie Li2 1Department of Cardiology, Zhongshan Hospital of Traditional Chinese Medicine, Zhongshan, People’s Republic of China; 2Department of Cardiology, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, People’s Republic of China; 3Department of Radiology, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, People’s Republic of China; 4School of Medicine South China University of Technology, Guangzhou, People’s Republic of China; 5Department of Cardiac Surgery, Guangdong Provincial People’s Hospital (Guangdong Academy of Medical Sciences), Southern Medical University, Guangzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jie Li; Jianfang Luo, Guangdong Provincial People’s Hospital, #96 Dongchuan Road, Yuexiu District, Guangzhou, Guangdong, 510080, People’s Republic of China, Tel +86 020 83827812, Email leomoku1981@163.com; jianfangluo@sina.comBackground: Left ventricular ejection fraction (LVEF) worsening after transcatheter aortic valve replacement (TAVR) was common in clinical practice. However, the effect of acute worsening LVEF is unclear.Methods: All consecutive patients who underwent TAVR between January 2016 and May 2022 were analyzed. Patients were divided into worsened LVEF and non-worsened LVEF according to whether or not they had an LVEF decline of ≥ 5% at discharge. Survival at follow-up was compared between two groups. Logistic regression analysis was used to determine independent predictors of worsening LVEF.Results: A total of 439 patients were included in the analysis, and 112 (25.5%) patients had worsened LVEF. Worsened LVEF was more common in patients with LVEF ≥ 50%. After multivariable logistic analysis, only baseline LVEF was associated with worsening LVEF [OR=1.06 (95% CI: 1.04– 1.08), P < 0.001]. The decline in LVEF recovered to the baseline after one month. There were no significant differences in survival between patients with and without worsened LVEF (Log rank P = 0.48).Conclusion: Acute worsening of LVEF after TAVR was not uncommon but did not affect survival. It could recover to baseline levels after one month. Routine post-TAVR echocardiography should focus on other metrics rather than acute LVEF changes.Keywords: aortic stenosis, transcatheter aortic valve replacement, left ventricular ejection fraction